Our developing world - Stamp, L Dudley (London : Faber and Faber, 1960)
The fundamental problem which faces the world today is the rapidly increasing pressure of population on physical resources,particularly on the resources of land
Includes index
obn21/01/2019
Loans
Keywords: Natural resources; Population; Food supply